Effect of Renal Impairment on the Pharmacokinetics of Firsocostat, an Acetyl‐Coenzyme A Carboxylase Inhibitor, and Cilofexor, a Selective Nonsteroidal Farnesoid X Receptor Agonist. (28th February 2023) - Weber, Elijah; Younis, Islam R.; Nelson, Cara; Ding, Dora; Qin, Ann; Xiao, Deqing; Watkins, Timothy R.; Othman, Ahmed A.
Abstract: Firsocostat, a liver‐targeted acetyl‐coenzyme A carboxylase inhibitor, and cilofexor, a nonsteroidal farnesoid X receptor agonist, are being developed in combination for treatment of nonalcoholic steatohepatitis. This phase 1 study evaluated firsocostat and cilofexor pharmacokinetics and tolerability in participants with severe renal impairment (SRI) and healthy matched controls (HMCs). Ten participants with SRI (estimated glomerular filtration rate by Modification of Diet in Renal Disease <30 mL/min/1.73 m 2 ), and 10 HMCs received single oral doses of firsocostat (20 mg) on day 1 and cilofexor (100 mg) on day 7 in a fasted state. Plasma concentrations of firsocostat (and nonactive metabolite GS‐834773) and cilofexor (and nonactive metabolites GS‐716070 and GS‐1056756) were collected over 96 hours and quantified; plasma exposures (area under the concentration‐time curve [AUC] and peak concentration [Cmax ]) and plasma protein binding were characterized. Firsocostat AUC was ≈40% higher in SRI versus HMC, while Cmax was 8% lower. Observed exposures of the firsocostat metabolite were ≈4.6‐fold higher in SRI participants versus HMC. Exposures (AUC and Cmax ) of cilofexor and metabolites and percentages of protein binding of all analytes were similar between SRI and HMC groups. Treatment‐emergent adverse events were generally mild and not considered related to study drug. A <50% increase in firsocostat exposure was observed among SRI participants but was deemed not clinically relevant. There was no apparent effect of SRI on cilofexor exposure. Based on this trial, firsocostat and cilofexor dosing are not expected to require modification in patients who are renally impaired.